MOTIVASI SISWA LAKI-LAKI DALAM MENGIKUTI PENGEMBANGAN DIRI SENI TARI DI SMA NEGERI 1 BATANG ANAI - Putri Yunengsih; Indrayuda Indrayuda; Afifah Asriati (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to explain and describe the motivation of male students in following self-development dance in SMA Negeri 1 Batang Anai. This type of research is qualitative research using descriptive method. The object of research is the development of male students themselves dance in class X in the SMA N 1 Shaft Mounds. The main instrument in this study is the researchers themselves and the instruments used such as: logger tool record book, and photo cameras. Engineering data collection done by the library study, observation, interviews, and documentation. Technique of data analysis was performed with data collection measures, the reduction of data, display data and conclusion/verification. The results showed that the cause of the low motivation of male students in learning the art of dance in SMA Negeri 1 Batang Anai was background knowledge of dance, the condition of the environment, and the motivation of teachers or less dance coach effective in self development of the art of dance. As a teacher or coach can motivate must dance, male students so interested in following the activities of the self development of this dance. By way of providing encouragement, care, individual approach to the male students in the form of praise and appear instantly as a model. With the motivation of teachers and the existence of latian exercises then so on male students will be able to perform the dance shamelessly or motivated to learn to dance.Keywords: Motivation, Male Students, Self Development, Dance